Pemanfaatan Limbah Cangkang Kerang Kijing Sebagai Bahan Campuran Beton - Putri Aisya Irwan; Febriani, Lisa; Tonapa, Suryanti Rapang (Paulus Civil Engineering Journal, 2025)
The use of natural materials and waste as an alternative to building materials is increasingly popular in the field of civil engineering because it can reduce environmental impact, save costs, and increase creativity in building design. As for the use of kijing shell waste as an additional material in concrete mixtures, it can be an environmentally friendly and innovative alternative. This study examines the use of kijing clam shell waste as an additive to cement in normal concrete to determine its effect on the properties of fresh concrete and mechanical properties for. The slump value varies by 0%, 3%, 6%, 9% respectively by 55mm, 56mm, 58mm, 60mm and the fill weight is 372.2576 kg/m3, 2390.961 kg/m3, 2380.5405 kg/m3 and 2398.4692 kg/m3, For hard concrete in the form of compressive strength, each variation has decreased by 20.81%, 40.06% and 56.521% against 0%, tensile strength decreased by 13.18%, 26.29% and 43.244% respectively against 0%, Flexural strength 16.072 %,26.78% and 35.71 % to 0 %, elastic modulus of 2.838 %, 10.561%, 23.140 % to 0 %. The increasing percentage of kijing shell waste can provide a small strength value of hard concrete.